Access to credit and the determinants of technical inefficiency among specialized small farmers in Chile - Rodrigo Saldias; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
The influence on technical efficiency of access to credit and public support policies is studied for two groups of specialized small farmers in Chile. Using 2004 data, translog stochastic frontier production functions for 109 livestock and 342 crop producers are estimated. Mean technical efficiency is 89% and 78% for crop and livestock producers, respectively. Technical efficiency increases with decreasing use of inputs, dependence on on-farm income, farmer education, family size and the age of the family head. Extension services do not appear to help farms become more efficient, and even reduce efficiency among specialised crop pro-ducers. The volume of credit increases efficiency in crop production and reduces it in live-stock production. Correspondingly, credit constrained farmers are less efficient in crop pro-duction and more efficient in livestock. These results may reflect the fact that investments in livestock production can involve considerable adjustment costs in the short run. For livestock producers, credit volume and credit constraints are found to be endogenous to technical effi-ciency. A possible explanation is the organisation of public support for small livestock pro-ducers in Chile, which provides lenders with information about individual livestock produc-ers. This might enable lenders to target loans on the basis of efficiency. Correcting for this endogeneity does not lead to qualitatively different results, but does influence point estimates of parameters in the production function and inefficiency models. This highlights the impor-tance of testing for endogeneity in the variables used to model inefficiency effects.
Keywords: 330